Perancangan Strategi Pengembangan Bisnis Bakery dengan Pendekatan Blue Ocean Strategy (Studi Kasus) - Nur Izzaty; Rr Seza Pramuditha; Hasan Yudie Sastra; Didi Asmadi (Performa: Media Ilmiah Teknik Industri, 2024)
The level of competition in market, particularly in the bakery industry, has become more intensive notably post the pandemic Covid-19. Meanwhile, the strategy implemented by the bakery businesses tends to be on the red ocean, the market in which each business competes each other exhaustively in order to win a market share and destroy others. BL is one of the bakeries in Langsa, Aceh Province. BL’s business has been declining gradually and facing intensive competition in the industry. Therefore, the purpose of this research is to design a business development strategy for BL to create a new uncontested market space by applying value innovation. The process of value innovation is implemented with the approach of Blue Ocean Strategy (BOS) and its application Blue Ocean Studio. The result of this research is a new strategy adjusted to the needs of the three tiers of noncustomers by eliminating the service factor whenever the customers choose the product, and eliminating the factor of strategic location; reducing product variation; enhancing texture and flavor variants, hospitality service, cleanliness and comfort, branding, and attractive bakery design; creating delivery services, products distribution, healthy products for diets, and providing seating facilities as well as coffee corner in the bakery.